A Queen and a Masque. Samuel Daniel’s The Vision of the Twelve Goddesses as a Mirror of Anne of Denmark’s Political Aims: Samuel Daniel’s The Vision of the Twelve Goddesses as a Mirror of Anne of Denmark’s Political Aims - Pepe, Paolo (Testo e Senso, 2024)
This study focuses on the role played by Anne of Denmark in the English court during the first years of the reign of James I and on her creative use of the masque to convey, in both symbolic and allegorical ways, the idea of herself as a subject endowed with a peculiar political identity. From this perspective, the article analyses The Vision of the Twelve Goddesses (1604) by Samuel Daniel - the first masque commissioned by the Queen - interpreting it as an attempt on Anne’s part to appear as the center of a power that, though subordinate to the King's authority, demands its own autonomy and a function complementary to that of the sovereign.